Peran Kepercayaan Terhadap Penggunaan Pengobatan Tradisional Pada Penderita Hipertensi Di Kota Bengkulu - Ervina, Lissa; Ayubi, Dian (UI Scholars Hub, 2018)
Background. Hypertension is a serious disease that causes death. In 2013, the National Basic Health Research showed 21,6% of Bengkulu City people have hypertension. Bengkulu Province is one of ten provinces which have greater number of traditional treatment outpatient including hypertension. Aim. This study aim is to access effect of believe to usage of traditional treatments among hypertension patient after controlling social demography characteristics. Method. The study selected randomly 190 respondents and interviewed them using questionnaire. All respondents is hypertension patients who visited Nusa Indah community health center in last six months. Data were analyzed used multiple logistic regression based on computer software. Result. The study found 66,8% respondents used multiple traditional treatment. Mean score of respondent’s believe in 56,2 (scale 100). In multivariate analysis, there is no statistically significant between respondent’s believe and traditional treatment usage. Meanwhile, respondent’s educational background has significant relationship to traditional treatment usage.